Antecedents and mediating role of IT service climate in IT service quality: A mixed methods study. (April 2021) - Wang, Xiaolei; Lu, Jiandong; Feng, Yuqiang; Liu, Luning
Highlights: A mixed-method study reveals the role of IT service climate in IT service quality. Job resources and personal resources positively affect IT service climate (ITSC). Customer contact frequency strengthens the influence of ITSC on IT service quality. ITSC fully mediates the effects of training, reward, IS support and hope. ITSC partially mediates the effect of self-efficacy. Abstract: Developing a strong and positive information technology (IT) service climate is important to ensure high-quality IT services. The influence of job resources and personal resources on the IT service climate and the mediating effect of the IT service climate on IT service quality were explored in this study qualitatively and quantitatively. Among the various job resource factors, we found that training, reward, and information system (IS) support can improve the IT service climate. Coworker support shows a non-significant effect on IT service climate. Among the personal resource factors, self-efficacy and hope have significantly positive effects on the IT service climate. Optimism and resilience do not appear to significantly affect the IT service climate. Our results confirm that the IT service climate is an important mediator in enabling certain antecedents to properly impact IT service quality. The IT service climate was found to fully mediate the effects of training, reward, IS support, and hope while partially mediating the effect of self-efficacy. The effect of the IT service climate on IT service quality is also strengthened by a high customer contact frequency. The results presented here may provide scholars and practitioners with a comprehensive, workable understanding of the IT service climate.